The epidemic of workplace violence against nurses: a narrative review - Kumar, Mahendra; Kumari, Anita (International Journal Of Community Medicine And Public Health, 2024)
Workplace violence (WPV) has become the new normal for nurses, significantly impacting their physical and mental health, as well as their ability to work effectively. The world health organization (WHO) reported that approximately 8-38% of nurses face some form of violence in their careers. Despite nurses providing direct care for individuals suffering from various life-threatening events, and even infectious diseases 90% of violent behavior originated from patients and their families. The trend of violence against nurses is growing dangerously. More than 80% of WPV incidents among nurses are not formally reported due to fear of being blamed no support from management and no awareness about hospital policies to report an incidence. The impact of WPV is deep over 20% of nurses are leaving their jobs due to rising incidents of violence. The true extent of violence against nurses is underreported. It's crucial to identify areas requiring in-depth analysis and to provide appropriate solutions.